Fragile hope: Seeking justice for hate crimes in India - Fuchs, Sandhya (Stanford, California: Stanford University Press, 2024)
"Against the backdrop of the global Black Lives Matter movement, debates around the social impact of hate crime legislation have come to the political fore. In 2019, the UN Commission on Crime Prevention and Criminal Justice urgently asked how legal systems can counter bias and discrimination. In India, a nation with vast socio-cultural diversity, and a complex colonial past, questions about the relationship between law and histories of oppression have become particularly pressing. Recently, India has seen a rise in violence against Dalits (ex-untouchables) and other minorities. Consequently, an emerging "Dalit Lives Matter" movement has campaigned for the effective implementation of India's only hate crime law: the 1989 Scheduled Castes/Scheduled Tribes Prevention of Atrocities Act (PoA). Drawing on long-term fieldwork with Dalit survivors of caste atrocities, human rights NGOs, police, and judiciary, Sandhya Fuchs unveils how Dalit communities in the state of Rajasthan interpret and mobilize the PoA. Fuchs shows that the PoA has emerged as a project of legal meliorism: the idea that persistent and creative legal labor can gradually improve the oppressive conditions that characterize Dalit lives. Moving beyond statistics and judicial arguments, Fuchs uses the intimate lens of personal narratives to lay bare how legal processes converge and conflict with political and gendered concerns about justice for caste atrocities, creating new controversies, inequalities, and hopes"--
The Prevention of Atrocities Act : a social genealogy -- Who owns the law? : politics and intimacies of atrocity cases -- The case that could not be : police translations at the margins -- (Re-)writing law's allegiance? : Rumors, deep truths, and strategic disobedience -- "You must not compromise!" : contested collectives and complex complicities -- Fields of massacre : a "hollow" law? -- Habits of hopefulness : legal labors for a better future.
Includes bibliographical references (pages 287-321) and index.
Keywords: India; Hate crimes -- Law and legislation -- India -- Rajasthan; Dalits -- Crimes against -- India -- Rajasthan; Sociology; Dalits -- Legal status, laws, etc. -- India -- Rajasthan; Dalits -- Political activity -- India -- Rajasthan